2014
DOI: 10.1007/s00382-014-2155-z
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of two types of La Niña on the NAO during boreal winter

Abstract: The present work identifies two types of La Niña based on the spatial distribution of sea surface temperature (SST) anomaly. In contrast to the eastern Pacific (EP) La Niña event, a new type of La Niña (central Pacific, or CP La Niña) is featured by the SST cooling center over the CP. These two types of La Niña exhibit a fundamental difference in SST anomaly evolution: the EP La Niña shows a westward propagation feature while the CP La Niña exhibits a standing feature over the CP. The two types of La Niña can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
104
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 72 publications
10
104
0
3
Order By: Relevance
“…It is reported that based on the current indices it is not easy to classify the two types of ENSO, especially for the two types of La Niña (Ren and Jin 2011;Zhang et al 2014b). Thus, none of the two documents are consensus for the selection of the EP and CP ENSO.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that based on the current indices it is not easy to classify the two types of ENSO, especially for the two types of La Niña (Ren and Jin 2011;Zhang et al 2014b). Thus, none of the two documents are consensus for the selection of the EP and CP ENSO.…”
Section: Methodsmentioning
confidence: 99%
“…Several indices have been used in the literature, considering different oceanic regions, such as Nino-3 (N3) (5°N-5°S, 150°-90°W) (Hoerlinget al 1997;Manzini et al 2006) or Nino-4 (N4) (5°N-5°S, 160°E-150°W) (Kug and Ham 2011;Zhang et al 2015). However, most recent studies used the Nino-3.4 (N3.4) (5°N-5°S, 170°-120°W) index from the National Centers for Environmental Prediction/Climate Prediction Center (NCEP/CPC) (e.g., Free and Seidel 2009;Butler and Polvani 2011;Garfinkel et al 2012;Butler et al 2014;Barriopedro and Calvo 2014;Domeisen et al 2015).…”
Section: A Event Detectionmentioning
confidence: 99%
“…Note that the classification for La Niña events is still controversial. Here we directly refer to the previous study (Zhang et al 2015). The winters for the different types of winter-mean ENSO indices are listed in Table 2.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…However, they were also divided into the two types in some studies (Ashok and Yamagata 2009;Yuan and Yan 2013), particularly if the decadal background is eliminated since 1980 . Indeed, the value of distinguishing the two types for either El Niño or La Niña events is clearest from their distinct global and regional climate impacts rather than their different SST patterns (Zhang et al 2015). From this point of view, both types of El Niño and La Niña events will be focused on in this study.…”
Section: Introductionmentioning
confidence: 99%